CANTIGA AO DESAFIO E ESTETIZAÇÃO DA FALA: NATUREZA, MODALIDADES, FUNÇÕES - Nogueira, Carlos (Organon, 2007)
In this article we offer a theory for the Portuguese “cantigas ao desafio” (“contest songs”, poetic dueling). We shall approach them on the individual level, insofar as they are a personal creative act, and on a community level, envisaging them as a sociocultural phenomenon. Its necessary and interdisciplinary and multifaced approach arises from a poetico-musical specificity that doesn't become exhausted in musical and techno-literary components alone. It is a playful and creative game with a lot of anthropological and sociological ingredients, it is poetry in action. The contest becomes a dialogical macro-poem made out of two individual oral poems, intermingled in an alternance of forces, of variable tensions and distensions. The textual dimension is the more visible materiality of an organic process obeying to laws of improvisation in which linguistical-literary elements take part (ars poetica, grammar, rethoric, stylistics, themes, etc.). But it also obeys to extratextual factors with which the contesters interact very closely (the audience and the technological apparatus involved in some performances for mediatic purposes).